Beyond Tax Compliance Integrating Tax Planning Risk Management and Revenue Enhancement Through Management Consulting - Bhavika Jalan; Harshita Kadel; Syed Bilal Uddin; Abdul Baqi (Involvement International Journal of Business, 2026)
The increasing complexity of tax regulations, global economic integration, and heightened fiscal transparency have transformed tax planning and compliance into strategic business concerns. Management consultants are increasingly engaged to help organizations navigate these challenges, yet their role is often conceptualized narrowly as technical tax advisory. This study employs a qualitative, literature-based research design using an integrative and thematic review of peer-reviewed academic publications from 2015 to 2025. Relevant studies were systematically analyzed to identify patterns, themes, and theoretical linkages concerning the strategic role of management consultants in tax planning, compliance, and risk management. The findings indicate that management consultants have evolved into strategic partners who integrate tax planning and compliance within enterprise risk management and corporate governance frameworks. Consultant-led tax strategies contribute to proactive risk mitigation, revenue stability, regulatory compliance, and business sustainability. Consultants also play a critical role in navigating regulatory complexity and emerging tax challenges, including digital economy taxation and crisis-driven fiscal policies. The results align with strategic management, risk management, institutional, and stakeholder theories, highlighting management consultants as key actors in transforming tax management into a value-creating and legitimacy-enhancing function. This reconceptualization underscores the importance of integrating tax governance with broader organizational strategy and performance objectives.